An Investigation into Dietary Fibre Intake, Bowel Function and Mood among a sample of Irish Adults - Sophie Mulligan; Ellen Lynch; Suzanne Doyle (SURE Journal: (Science Undergraduate Research Experience Journal))
Background Previous studies have examined the relationship between dietary fibre intake and mood and bowel function separately, however, no cross-sectional study has yet explored the relationship between all three variables. This study examines the association between dietary fibre intake, bowel function and mood in a cohort of Irish adults at a university campus. Methods A cross-sectional study was conducted. An online questionnaire was distributed to staff and students of TU Dublin through email and publicised using posters. Three validated surveys were used in the design of the questionnaire, to assess dietary fibre intake, mood and bowel function. All staff and students of TU Dublin were eligible to participate. Data was collected between the 28th of February and the 13th of March 2023. One-way ANOVA and Independent Samples T-Tests were used to examine the association between the variables and demographic characteristics. Results A total of 275 responses were received. The majority of those who participated were female (69%) and members of the Faculty of Sciences and Health (66.5%). The mean dietary fibre intake of the study cohort was 20.01g/day (SD=11.9g/day). Fifty-four percent of the study cohort reported feeling happy at the time of the questionnaire. A significant association between dietary fibre intake and faculty of study was identified, with those in the Faculty of Sciences and Health having significantly higher intakes than all other faculties (P=0.022). A significant positive association between mean dietary fibre intake and mood status was observed (P=0.009), with those who were happy having a higher mean daily intake of fibre than those who were unhappy and not particularly happy/unhappy (P = 0.039 and P = 0.032, respectively). Significant differences in mood status between each bowel function status were also observed, with those who were happy having significantly better bowel function scores than those who were unhappy and not particularly happy/unhappy (both P < 0.001). Conclusion In this cross-sectional study, dietary fibre intake was found to be largely insufficient amongst Irish adults. Our findings suggest a significant association between both dietary fibre intake and mood and bowel function and mood, however further research is required to elucidate the interplay between all three factors.